CRITERIA OF CHOICE OF VITAMINS AND MINERALS COMPLEXES IN PEDIATRIC PRACTICE - A. A. Trubnikov; S. V. Talashova ("Paediatrician" Publishers LLC, 2011)
The need of vitamin and mineral correction of diet in adults and children in Russian Federation is obvious for physicians and pediatricians. The main problem in the present times is not only necessity of vitamins and minerals complexes (VMCs) administration but compliance of the products with proper standards. Optimal compound of VMCs, content of several ingredients, possibility of selection of drug for specific problem by a doctor or a pharmacist (as VMCs are the out-of-prescription drugs), convenient dosage form and organoleptic characteristics making the drug easy-to use are significant. Clearness of proposed material is confirmed by description of VMC Pikovit as popular drugs among patients and specialists.